Kebijakan Perencanaan dan Penganggaran Dana BOS Madrasah Swasta di DIPA Direktorat Jenderal Pendidikan Islam Kementerian Agama - Sulistya Hady, Danang (JURNAL ILMIAH GEMA PERENCANA, 2024)
This policy paper examines the BOS fund planning and budgeting policies of private madrasahs with a focus on four main issues, namely: (1) transparency and accountability of fund management, (2) suitability of allocation to madrasah needs, (3) timeliness of fund disbursement, and (4) capacity of human resources managing BOS in madrasahs. This paper uses qualitative methods with a case study approach and policy analysis methods, including SWOT analysis, to identify internal (strengths and weaknesses) and external (opportunities and threats) factors that influence the effectiveness of the policy. The results show that although the BOS policy has made a positive contribution to increasing access to education, there are still several weaknesses that need to be addressed. Lack of transparency and accountability, mismatched allocation, late disbursement, and limited human resource capacity are the main challenges. Therefore, this study recommends several improvements, including: (1) strengthening the online information and publication system to increase transparency, (2) revising the fund allocation formula, and strengthening the process of preparing the Madrasah Work Plan and Budget (RKAM) based on needs, (3) simplifying the administrative process and improving coordination between agencies to accelerate fund disbursement, and (4) increasing human resource capacity through training and mentoring.